Validity and reliability of anxiety literacy (A-Lit) and its relationship with demographic variables in the Iranian general population - Jafari, Alireza; Moshki, Mahdi; Mokhtari, Ali Mohammad; Naddafi, Fatemehzahra; Nejatian, Mahbobeh (Frontiers in Public Health, 2024)
Abstract Introduction: Anxiety disorder is one of the most common mental disorders. This cross- sectional research aimed to determine anxiety literacy (A-Lit) psychometric properties among the Iranian population in 2022. Methods: This research was conducted on 690 people in Iran in 2022. In this study, people were selected by proportional stratified sampling, and the validity and reliability of the A-Lit designed by Griffiths were assessed. Validity of A-Lit was assessed by face validity, content validity, and confirmatory factor analysis. Reliability of A-Lit was evaluated by the McDonald's omega coefficient, Cronbach’s alpha coefficient, and test– retest. In analytical sections, the tests of One-way ANOVA, Chi-squared test, and independent samples t-test were used. Results: The rates of S-CVI/Ave and CVR for A-Lit were 0.922 and 0.774, respectively. In confirmatory factor analysis, three items were deleted because the factor loading was less than 0.4, and goodness-of-fit indexes (Some of goodness-of-fit indexes: χ2/df = 4.175, GFI: .909, RMSEA= .068, PCFI= .745, AGFI = .883) were confirmed as the final model with 19 items. For all items, the Cronbach’s alpha coefficient was 0.832, the McDonald's omega coefficient was 0.835, and the intraclass correlation coefficient was 0.874. According to the results of this study, 1.3 % (n= 9) did not answer any questions correctly. 8.4 % (n= 58) were able to answer 1 to 6 questions correctly. Approximately 72 % (n= 495) were able to answer 7 to 12 questions, and eventually only 18.6 % (n=128) were able to answer 13 questions and more. There was a significant relationship between sex, age group, occupation status, marital status, and get information related to mental illness with A-Lit level (p<0.05). Conclusion: The Persian version of A-Lit was confirmed with 19 items, and this scale is a reliable tool for measuring A-Lit in the general population. The results also showed that a few people have a higher level of anxiety literacy and that educational and intervention programs need to be designed and implemented for the public population.